Maintaining Malay Culture amidst the Current of Globalization - Aditia, Fanita (Manunggal Halim Jaya, 2024)
This globalization has led to political, economic and cultural integration. Malay culture is now being hit by globalization. This is because many foreign cultures have been allowed to enter regions that have a Malay feel, both through print media and electronic media. With the fading of Malay culture, the identity of the Malay community has also faded, which is characterized by people who are innocent, polite, modest, and able to adapt to various cultures without letting go of their Malayness. The aim of this article is to explain the efforts that can be made to preserve Malay culture amidst the rapid flow of globalization. This paper uses library research research methods. The results of this research are that the process of preserving Malay culture must of course come from public awareness first, then it can be done by means of culture experience and culture knowledge.